2019
DOI: 10.1016/j.bbmt.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Predicting the Adverse Effects of Chimeric Antigen Receptor T Cell Therapy in Patients with Non-Hodgkin Lymphoma

Abstract: CD19-targeting chimeric antigen receptor (CAR)-T cell therapy has shown great efficacy in patients with relapsed/ refractory non-Hodgkin lymphoma (NHL) but has been associated with serious adverse effects, such as cytokine release syndrome (CRS). It has been speculated that NHL baseline disease burden might affect clinical outcome and CRS, but this has not been explored in detail in any previous study. Metabolic tumor volume (MTV) and total lesion glycolysis (TLG), as measured by fluorodeoxyglucose positron em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 22 publications
5
89
3
Order By: Relevance
“…We did not note any noticeable changes in brain metabolism in patients having experienced neurotoxicity, and PET was performed at a later time point (Day 30) in this study. In a study including 19 patients, Wang et al reported that patients with higher baseline disease burden as determined by FDG PET (both baseline MTV and TLG) had more severe CRS [15]. We did not observe a significant association with disease burden in a smaller patient cohort.…”
Section: Discussioncontrasting
confidence: 85%
“…We did not note any noticeable changes in brain metabolism in patients having experienced neurotoxicity, and PET was performed at a later time point (Day 30) in this study. In a study including 19 patients, Wang et al reported that patients with higher baseline disease burden as determined by FDG PET (both baseline MTV and TLG) had more severe CRS [15]. We did not observe a significant association with disease burden in a smaller patient cohort.…”
Section: Discussioncontrasting
confidence: 85%
“…Using the TMTV41% method, the optimal threshold for early relapse, in terms of false-positive and false-negative predictions, in our series was 80 mL. The putative prognostic impact of TMTV in patients treated with CAR T cells has been suggested in a series of only 19 patients, 21 in which TMTV tended to be lower in responding patients. Interestingly, median TMTV in this study was 72 mL and, thus, very close to our own data.…”
Section: Discussionmentioning
confidence: 77%
“…The novel CAR‐T cells therapy has shown great efficacy in RR‐RCHOP DLBCL patients. The drawback of this therapy is patients may develop “cytokine release syndrome” which could cause false positive results on PET/CT scans 43 . Nevertheless, an explorative study on patients treated with CAR‐T cells therapy showed that “cytokine release syndrome” does not confound post‐treatment PET/CT scan findings.…”
Section: Discussionmentioning
confidence: 99%